Produção animal e dinâmica vegetacional em pastagem natural sob diferentes sistemas de manejo - Brum, Marcos da Silva (2006)
The trial was accomplished in the Fundação Estadual de Pesquisa Agropecuária (FEPAGRO) in São Gabriel, RS, to evaluate the performance of sheep and lambs in natural grassland, managed with different grazing systems and, pasture improvement with fertilization and introduction of cool season species, and to verify the effects of those different managements on the dynamics of this grassland ´s floristic composition. The treatments were as follows: natural grassland improvement with introduction of annual ryegrass (Lolium multiflorum Lam cv. Comum), red clover (Trifolium pratense L. cv. E-116) and birdsfoot trefoil (Lotus corniculatus L. cv. São Gabriel) under rotative grazing (CNM); natural grassland under continuous grazing (CNC) and natural grassland under rotative grazing (CNR). The treatments were distributed in an entirely randomized design, with two replicates. There was a delay of the beginning of the use of the grassland in function of structural problems as the delay in fencing paddocks of the treatments with rotative grazing. The experimental period was from 11/01 to 12/23/2004. Grazing animals were ewes with lambs (males and females), of Corriedale breed. The data were submitted to multivariate analysis based in ordination and randomization testing. Significant difference was not observed between the treatments for the avarage values of pasture growth rate (P=0,3332) and total production of DM (P=0,3391). The averages forage allowances of 20,3 and 22,1 kg of DM/100 kg of live weight in CNM and CNR, respectively, were superior to 13,7 kg of DM/100 kg of live weight verified in CNC. Significant difference among the treatments was not observed in the values of DLG (Daily Liveweight Gain) for male (P=0,5724) and females (P=0,2488) lambs. For the analyses of botanical composition, in the first evaluation CNM differed (P=0,0001) from CNC and CNR, while in the second evaluation the observed difference (P=0,0017) was between CNM and CNC. The results of DLG and gain per area were affected by the delay of the beginning of the experiment and by the drought observed during the experimental period, especially in the natural grassland with introduction of cool season species. The results of DLG of lambs, obtained in the natural grassland under continuous grazing, permits to consider the reals allowance around 14% to correspond to the best potential of animal production in natural grassland. The effect of rotational grazing, introduction of species and fertilization is decisive for changes in the composition of the vegetation.